1981
DOI: 10.1111/j.1471-0528.1981.tb01766.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary Carcinoma of the Fallopian Tube

Abstract: Summary Twenty‐two patients with primary carcinoma of the Fallopian tube treated at the Royal Marsden Hospital are reported. The age distribution, parity and variety of presentation of the disease were in accordance with previous reports in the literature. Overall survival at 5 years was 48% and the place of radiotherapy and chemotherapy in its management remains to be established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1
5

Year Published

1985
1985
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 6 publications
0
16
1
5
Order By: Relevance
“…Primary malignant tumors of the fallopian tube account for 0.3-1.9% of gynecological malignancies (6). Benign tumors of the fallopian tube are even less common, the majority being adenomatoid tumors (7).…”
Section: Discussionmentioning
confidence: 99%
“…Primary malignant tumors of the fallopian tube account for 0.3-1.9% of gynecological malignancies (6). Benign tumors of the fallopian tube are even less common, the majority being adenomatoid tumors (7).…”
Section: Discussionmentioning
confidence: 99%
“…There are very few data that are extractable from the literature with regard to PFTC. Several authors using cisplatin-based chemotherapy in patients with advanced PFTC reported overall responses rates of 53%-92% [4,49,50,68,70,92,94,96,99]. Peters et al [50] reported a 75% complete response rate in a study of 46 patients with advanced or recurrent PFTC.…”
Section: Combination Chemotherapy For Advanced Diseasementioning
confidence: 99%
“…Primary fallopian tube carcinoma (PFTC) is an uncommon tumor accounting for approximately 0.14%-1.8% of female genital malignancies [1][2][3][4][5][6][7]. It is estimated, based on the data obtained from nine population-based cancer registries in the U.S., that the average annual incidence of PFTC is 3.6 per million women per year [8].…”
Section: Introductionmentioning
confidence: 99%
“…Deppe et al (1980) described two patients with advanced adenocarcinoma of the fallopian tube treated with a combination of adriamycin, cis-platinum, cyclophosphamide and progestin who achieved a complete pathological remission. Raju & Wiltshaw (1981) reported one complete pathological remission and one partial remission in 2 of 4 patients treated with cis-platinum. The two non-responders in their study were given cis-platinum at a low dose (20 mg/M2) in combination with chlorambucil.…”
Section: Discussionmentioning
confidence: 99%
“…Primary adenocarcinoma of the fallopian tube is a rare tumour of the female genital tract, with a reported incidence between 0.3% and 1.6% (Raju & Wiltshaw 1981). The prognosis following surgery remains poor (Schiller & Silverberg 1971), and due to the rarity of the tumour the efficacy of adjuvant radiotherapy and chemotherapy is not yet established.…”
Section: Introductionmentioning
confidence: 99%